No implication of HIV coinfection on the plasma exposure to rifampicin, pyrazinamide, and ethambutol in tuberculosis patients - Glauco Henrique Balthazar Nardotto; Valdes Roberto Bollela; Adriana Rocha; Oscar Della Pasqua; Vera Lucia Lanchote (Wiley, 2022)
Abstract There are contrasting findings regarding the effect of HIV on the pharmacokinetics of first‐line anti‐tubercular drugs (FLATDs) due to a lack of prospective controlled clinical studies, including patients with tuberculosis (TB) and patients with TB living with HIV. This study aims to assess the effect of HIV coinfection and antiviral therapy on the plasma exposure to FLATDs in patients with TB. HIV negative (TB‐HIV− group; n = 15) and HIV positive (TB‐HIV+ group; n = 18) adult patients with TB were enrolled during the second month of FLATDs treatment. All TB‐HIV+ patients were on treatment with lamivudine, tenofovir (or zidovudine), and raltegravir (or efavirenz). Serial blood sampling was collected over 24 h and FLATDs pharmacokinetic parameters were evaluated using noncompartmental methods. In the TB‐HIV+ patients, dose‐normalized plasma exposure area under the curve from zero to 24 h (nAUC0-24; geometric mean and 95% confidence interval [CI]) values at steady‐state to rifampicin, pyrazinamide, and ethambutol were 18.38 (95% CI 13.74-24.59), 238.21 (95% CI 191.09-296.95), and 18.33 (95% CI 14.56-23.09) µg∙h/ml, respectively. Similar plasma exposure was found in the TB‐HIV− patients. The geometric mean and 90% CI of the ratios between TB‐HIV− and TB‐HIV+ groups suggest no significant pharmacokinetic interaction between the selected antivirals and FLATDs. Likewise, HIV coinfection itself does not appear to have any effect on the plasma exposure to FLATDs.